1961
DOI: 10.1111/j.1365-2494.1961.tb00226.x
|View full text |Cite
|
Sign up to set email alerts
|

The Production of Early Spring Grass

Abstract: The effects of autumn management and nitrogenous manuring on the production of early spring grass were studied from 1954 to 1957 on farms throughout England and Wales. The most important management factor influencing spring yields was the application of spring nitrogen. In the early spring 6 to 10 lb. of dry matter were produced per lb. of nitrogen applied. Autumn nitrogen increased herbage yields in the auttimn by 8 to 17 lb. of dry matter per lb. of nitrogen applied. Italian and perennial ryegrass responded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1963
1963
1979
1979

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Experimental and practical experience has shown that early and late applications of nitrogenous fertilizer produce earlier grass in the spring and later grazing in the autumn than can be obtained from grass/clover swards which do not receive fertilizer nitrogen (Baker et ai,1,2). These applications of N are invariably associated with the suppression of clover to a greater or lesser extent.…”
Section: Introductionmentioning
confidence: 99%
“…Experimental and practical experience has shown that early and late applications of nitrogenous fertilizer produce earlier grass in the spring and later grazing in the autumn than can be obtained from grass/clover swards which do not receive fertilizer nitrogen (Baker et ai,1,2). These applications of N are invariably associated with the suppression of clover to a greater or lesser extent.…”
Section: Introductionmentioning
confidence: 99%
“…Where sites are not completely occupied, or are occupied to a greater than optimum level, defoliation, by stimulating vegetative reproduction or reducing occupancy to a more favourable level, may increase production (6). Baker et al (2) found the effects of autumn grazing on spring yields of cocksfoot/ timothy/meadow-fescue swards were inconsistent, although in one year out of three there was some evidence that resting benefited spring growth. With ryegrass swards, however, higher spring yields were obtained from swards grazed in the autumn than from those rested.…”
Section: Discussionmentioning
confidence: 99%